Policy Implementation in Preventing Plagiarism in Students in the Digital Age - Faizal Pikri; Disa Maulida Insani; Cecep Wahyu Hoerudin (Iapa Proceedings Conference, 2022)
The act of plagiarism or copying other people's work via the internet is a phenomenon that has been around for a while among students; in making scientific work assignments, not a few students plagiarism or copy-paste from the internet so that the task is immediately resolved. The purpose of this research was to find out how the State Islamic University Sunan Gunung Djati Bandung's efforts to prevent and deal with plagiarism in the midst of the digitalization era. Therefore, another objective of this research is to determine whether the State Islamic University of Sunan Gunung Djati Bandung students are capable and understand digital literacy. So far, the efforts made by the State Islamic University Sunan Gunung Djati have been quite good in preventing plagiarism by making policies on the percentage of plagiarism and also providing sanctions for students who commit plagiarism. However, some students still feel they need help understanding how to avoid plagiarism. In addition, some students have understood digital literacy. However, its application still needs to be improved, such as being often influenced by fake news or hoaxes and students' lack of interest in studying the truth of information on the internet for reference to scientific papers because it is considered to take a long time.